Ion-Exchange Synthesis of Water-Dispersible WO3 for Sonocatalyst Applications - Zhang, Feng-Jun; Xu, Hai-Yan; Mei, Sheng-Fu; Dong, Hong-Fei; Meng, Ze-Da; Oh, Won-Chun (Asian Journal of Chemistry, 2013)
Water-dispersible tungsten (VI) oxide (WO3) catalysts of orthorhombic crystal structure has been synthesized by calcination at 200 ºC and 500 ºC, of H2WO4 prepared from ion-exchange with strong acidic cation resin. The water-dispersible WO3 catalyst was also found to exhibit interesting sonocatalytic properties for degradation of different kinds of dye (cationic dye rhodamine-B and anionic dye methyl orange) under ultrasonic irradiation. First, its sonocatalytic activity was higher than that of P25 (a commercial P25 as a benchmark) for cationic dye rhodamine-B, whereas it was lower for anionic dye methyl orange sonodegradation compared with P25. Second, almost no photochromic response of the WO3 was detected after ultrasonic in rhodamine-B solution. The results were discussed in terms of the characterization data of water-dispersible WO3 towards which, the role of the dye solution chemistry is also examined.